Pelatihan Pengajaran Keterampilan Menggunting Dasar Bagi Guru SLB Di Lampung - Ossy Firstanti Wardany; Yulvia Sani (Universitas Mathla'ul Anwar Banten, 2022)
TRAİNİNG FOR SPECİAL EDUCATORS ON TEACHİNG CUTTİNG SKİLLS İN LAMPUNG. Scissor skills in children with special needs have challenges and problems for teachers in special schools. Children with sensomotory problems often experience difficulty in scissor skills. In fact, cutting plays a role in training fine motor skills, especially writing. This activity aims to educate and provide understanding to special school teachers about teaching scissor skills for children with special needs. The subjects in the activity were special school teachers in Lampung. The activity was carried out online for two meetings. The training is in the form of material presentation, demonstration videos, question and answer, and assignments. The first material consists of the concept of cutting, the development of scissors skills in children, assessment of cutting skills, stages of teaching scissors and cutting worksheets. The results of the activity evaluation showed an increase in the participants' abilities related to scissors knowledge, the results of good participant assignments, and positive and constructive feedback.